Quality affecting factors of RNA – its assessment and influence on PCR reactions - Poovakka, Sheethel Kunnath; Ramadas, Durga; Ramadas, Gouri; VG, Deepak Roshan (International Journal of Scientific Research in Biological Sciences, 2018)
Good quality of RNA is the prime concern in molecular biology research works and clinical diagnosis. Different organic solvents and salt are used for RNA-isolation. Presence of different organic solvents like phenol, trizol, chloroform, isopropanol, ethanol and salt like EDTA in RNA may affect the downstream processes. The effect of these different organic solvents and EDTA on the quality /integrity of RNA and its effect on qualitative and qPCR has been evaluated in our study. We have found that the trace contamination with phenol and trizol in isolated RNA has inhibited the qPCR and its contamination in RNA cannot be identified merely by inspecting the A260:A280 and A260:A230 ratios. However, by evaluating the absorbance peak-pattern using UV absorbance between 220-340 nm, we can differentiate phenol/trizol contaminated RNA. Also, an overestimation (4-200 fold) of nucleic acid was observed for phenol and trizol-treated RNA in our study. Absorbance peak-pattern variations could only identify higher concentrations of EDTA in RNA, but for lower concentrations, it remains undetectable and higher concentrations of EDTA in RNA have shown to inhibit real-time PCR and alter the Ct value at its lower concentration. RNA contaminated with ethanol, isopropanol, chloroform cannot be distinguished even from the peak-pattern analysis and the UV-absorbance ratios. Higher concentration of alcohol decreased the PCR efficiency by huge variation in Ct values whereas lower concentrations did not show much effect. Surprisingly, the RNA integrity on agarose gel remained intact with all the organic solvents and EDTA-treated RNA.